Common but differentiated rights and responsibilities in tuna fisheries management. Issue 1 (25th September 2021) - Sinan, Hussain; Bailey, Megan; Hanich, Quentin; Azmi, Kamal
Abstract: The UN Law of the Sea Convention (LOSC) and one of the implementing agreements of the Convention—the UN Fish Stocks Agreement (UNFSA)—mandates all states to cooperate in the management of highly migratory and straddling fish stocks. In doing so, the UNFSA specifies that the special requirements of developing states need to be taken into account. To date, except in the Western and Central Pacific Fisheries Commission (WCPFC), there is no formal mechanism to identify these differential responsibilities in tuna regional fisheries management organizations (RFMOs). Although some conservation and management measures exempt small‐scale and artisanal fishing vessels, power imbalances within RFMOs tend to favour the interests of more developed and larger distant water fishing nations over those of small developing coastal states. To facilitate the implementation of differentiated responsibilities as mandated in UNFSA, in this study we develop a three‐step framework that could be applied in the case of new conservation and management measure proposals. The framework has also been tested based on two developing countries and compared with a developed state in the Indian Ocean Tuna Commission and the adopted resolutions in 2019. To facilitate better transparency and equitable decision‐making processes across RFMOs, this framework could be adapted based on member states' fisheries management objectives and target and non‐target species.